Cracking under Pressure? Gender Role Attitudes toward Maternal Employment in Times of a Pandemic - Natalia Danzer; Mathias Huebener; Astrid Pape; C. Katharina Spiess; Nico A. Siegel; Gert G. Wagner (Institute of Labor Economics (IZA), 2021)
This paper studies the effects of Covid-19 related daycare and school closures on gender role attitudes toward maternal employment in Germany. We compare women and men with dependent children to those without children one year after the outbreak of the pandemic. Using data on gender role attitudes from 2008 through 2021, we find that fathers' egalitarian attitudes toward maternal employment dropped substantially in 2021. This drop is observed for men in West Germany, who showed a steady progression toward more egalitarian attitudes in the pre-pandemic period. Attitudes by women are not affected. These findings suggest that the pandemic not only affected the short-term allocation of housework and childcare, but also reversed recent trends toward more egalitarian gender roles.
Keywords: J13; J16; J18; J22; 330; COVID-19; gender role attitudes; childcare; difference-in-difference; ALLBUS; COMPASS